2020
DOI: 10.3390/ph13100276
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Benefits of Vonoprazan as Helicobacter pylori Infection Therapy

Abstract: Helicobacter pylori infection is a severe global health problem that is closely associated with acid-related diseases and gastric malignancies. Eradicating H. pylori is strongly recommended for lowering peptic ulcer recurrence and preventing gastric cancer. The current approved H. pylori eradication regimen combines a proton pump inhibitor (PPI) with two antibiotics. Unfortunately, this regimen failed to meet expectations mostly due to antibiotic resistance and insufficient gastric acid suppression. Vonoprazan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 95 publications
0
19
0
1
Order By: Relevance
“…The regimens achieved above 91% cure for those who previously failed eradication treatment. Many (85%) patients received higher doses of amoxicillin (1125 mg t.i.d) and vonoprazan (20 mg t.i.d) than those that had been used amoxicillin (750 mg b.d) and vonoprazan (20 mg b.d) previously 37,38 and could be responsible for the outcomes in those regimens. To our knowledge, our protocol's result is the highest first-line eradication rate and our findings are similar to the previously reported efficacy of vonoprazan-containing therapies for the eradication of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regimens achieved above 91% cure for those who previously failed eradication treatment. Many (85%) patients received higher doses of amoxicillin (1125 mg t.i.d) and vonoprazan (20 mg t.i.d) than those that had been used amoxicillin (750 mg b.d) and vonoprazan (20 mg b.d) previously 37,38 and could be responsible for the outcomes in those regimens. To our knowledge, our protocol's result is the highest first-line eradication rate and our findings are similar to the previously reported efficacy of vonoprazan-containing therapies for the eradication of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…39 Previous reports have shown that when vonoprazan-containing regimens were used in first-line and second-line treatment, eradication rates were between 83%-96% and 72%-96%, respectively. 37,38 In addition, one study reported 100% eradication in 19 patients with two failed therapies before being treated with vonoprazan (20 mg), amoxicillin (750 mg), and rifabutin (150 mg) twice daily for 10 days. 40 In addition to the role of vonoprazan itself, the high efficacy achieved from the vonoprazan-containing therapies reported in this study compared to previously published literature may be due to several other factors including treatment duration, type of antibiotics used along with their relative dosages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of action is different from that of PPIs. Conventional PPIs require 3-5 d to achieve maximal and steady-state gastric acid inhibition, whereas P-CABs increase the intragastric pH to nearly 7 within four hours[ 80 ].…”
Section: Up-to-date Research On H Pylori Therapymentioning
confidence: 99%
“…Helicobacter pylori (Hp) is a flagellated Gram-negative and spiral-shaped bacterium that is colonized in the stomach, which is one of the most common chronic bacterial infections in humans, affecting approximately 4.4 billion individuals worldwide [ 1 , 2 ]. In China, approximately 50% to 80% of the population is infected with Hp, and the rate is still rising [ 3 ].…”
Section: Introductionmentioning
confidence: 99%